Advances in capillary electrophoresis for plant analysis - Tůma, Petr (Talanta, 2025)
Capillary and microchip electrophoresis plays an important role in the analysis of the chemical composition of plants and nutrient soils, which finds applications in plant physiology, agrochemistry, medicine, toxicology and food science. Electrophoretic methods are used to determine minerals such as nutrients, heavy metal ions, primary and secondary metabolites, herbicides, phytohormones, peptides, proteins and extracellular vesicles. Progress is particularly evident in the following topics: i) development of mobile electrophoretic analysers for field-based monitoring of soil mineral supply, ii) direct analysis of xylem sap without sample treatment, iii) coupling of capillary and microchip electrophoresis with mass spectrometry for comprehensive metabolome and proteome characterization, iv) determination of secondary metabolites as biologically active compounds with a range of therapeutic and toxicological effects, v) monitoring of herbicides and their degradation dynamics, vi) research on plant exudates, extracellular vesicles and specific protein interactions.
Keywords: Mass Spectrometry; rostliny; hmotnostní spektrometrie; Plants; Minerals; Phenolics; Capillary electrophoresis; Plant; herbicidy; Glyphosate; Soil; Electrophoresis, Capillary; Herbicides; elektroforéza kapilární; Detection